A dorsomedial prefrontal cortex-based dynamic functional connectivity model of rumination - Jungwoo Kim; Jessica R. Andrews-Hanna; Hedwig Eisenbarth; Byeol Kim Lux; Hong Ji Kim; Eunjin Lee; Martin A. Lindquist; Elizabeth A. Reynolds Losin; Tor D. Wager; Choong-Wan Woo (Nature Communications, 2023)
Abstract Rumination is a cognitive style characterized by repetitive thoughts about one’s negative internal states and is a common symptom of depression. Previous studies have linked trait rumination to alterations in the default mode network, but predictive brain markers of rumination are lacking. Here, we adopt a predictive modeling approach to develop a neuroimaging marker of rumination based on the variance of dynamic resting-state functional connectivity and test it across 5 diverse subclinical and clinical samples (total n = 288). A whole-brain marker based on dynamic connectivity with the dorsomedial prefrontal cortex (dmPFC) emerges as generalizable across the subclinical datasets. A refined marker consisting of the most important features from a virtual lesion analysis further predicts depression scores of adults with major depressive disorder (n = 35). This study highlights the role of the dmPFC in trait rumination and provides a dynamic functional connectivity marker for rumination.